Predicting Dual-WAN Failover Using a Variant of the RNN Algorithm for High-Availability Internet Networks - Tumbuh Tumbuh (Eduvest - Journal of Universal Studies, 2026)
The availability of the Internet network is very necessary for daily activities and in the business world. The need for the internet has been very massively used both with cell phones, personal computers and network computers using network hardware. One of the network hardware used in this study is a microtia router as load balancing. Failover prediction analysis with dual WAN to obtain Internet network availability using the RNN variant algorithm method to support stability performance in using the internet. Internet Service Provider (ISP) is an internet provider service used in this study, ISP Indihome 20 Mbps and ISP Telkomsel Modem Orbit GSM model HKM0130 use 4G prepaid cards as internet service providers. The purpose of this study is to predict the redirection of the internet from dual WAN to support the availability of the Internet network. With the stability method using algorithm support, this research provides convenience and algorithms in network reliability configuration. The results show that load balancing with PCC and ECMP methods combined with failover mechanisms significantly improves network performance. For 100 users, throughput increased from 90 Mbps to 180 Mbps, response time decreased from 150 ms to 70 ms, and packet loss dropped from 5% to 2%. The failover mechanism successfully maintains connectivity when one ISP line fails. In conclusion, the dual-WAN failover system with RNN-based prediction effectively ensures high-availability internet networks with proven reliability. The application of research results can be carried out by companies and education providers as well as for other needs.